2005
DOI: 10.1093/jn/135.3.603
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soy Consumption on the Urinary 2:16-Hydroxyestrone Ratio in Postmenopausal Women Depends on Equol Production Status but Is Not Influenced by Probiotic Consumption

Abstract: Some epidemiologic studies reported an association between a low ratio of urinary 2-hydroxyestrogens (2-hydroxyestradiol + 2-hydroxyestrone) to 16alpha-hydroxyestrone (2:16OHE(1)) and increased breast cancer risk. Some studies show that soy consumption increases this ratio, and it is suggested that this effect may reduce breast cancer risk. We hypothesized that consumption of probiotic bacteria would alter fecal bacteria and enzymes involved in soy isoflavone metabolism, thereby increasing isoflavone bioavaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 42 publications
3
43
1
Order By: Relevance
“…The effect of EPA and DHA on estrogen metabolism might be different and needs further investigation. The 6-week duration of intervention was short in this study; however, the metabolic pathway of estrogens was found to be altered in 7 days by indole-3-carbinol (Michnovicz et al, 1997), 12 days by broccoli diet (Kall et al, 1996), 4 weeks or 6 weeks by soy (Lu et al, 2000a;Nettleton et al, 2005). Therefore, 6-week intervention in this study might be adequate.…”
Section: Estrogen Metabolitesmentioning
confidence: 76%
“…The effect of EPA and DHA on estrogen metabolism might be different and needs further investigation. The 6-week duration of intervention was short in this study; however, the metabolic pathway of estrogens was found to be altered in 7 days by indole-3-carbinol (Michnovicz et al, 1997), 12 days by broccoli diet (Kall et al, 1996), 4 weeks or 6 weeks by soy (Lu et al, 2000a;Nettleton et al, 2005). Therefore, 6-week intervention in this study might be adequate.…”
Section: Estrogen Metabolitesmentioning
confidence: 76%
“…The first, a small controlled intervention trial (n = 34 postmenopausal women) by Nettleton et al (41), showed that soy protein supplementation resulted in increased urinary 2-hydroxy estrogens and an increased ratio of excreted 2:16 hydroxy-estrogens in the subgroup of participants who excreted high levels of equol. Whereas prospective studies have not consistently supported an association of circulating levels of these particular estrogen metabolites or their ratio with breast cancer risk (42)(43)(44), a growing body of research supports a role in breast carcinogenesis for the quinones of catechol estrogens, which are unstable and therefore difficult to measure directly in an epidemiologic setting (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…The other hypothesis for breast cancer protection by isoflavones and equol is that both may alter oestrogen metabolism away from the genotoxic oestrogen metabolites (increased risk) toward the protective metabolites (that decrease the risk of breast cancer) [101][102][103][104][105]. Xu et al showed that a diet rich with isoflavones reduced the synthesis of genotoxic metabolites 16a-OH E1 and 4-hydroxyestrogens, increased the synthesis of the protective metabolite 2-OH E1, and lowered the ratio of 2-OH E1 to 16a-OH E1 (also known to be protective for breast cancer) in both pre-and postmenopausal women [101,102].…”
Section: Breast Cancermentioning
confidence: 99%